Isolation and Identification of Microorganisms Associated with Faecal Droppings of Broiler Fed with Feed Compounded with Mineral-Fortified Pleurotus ostreatus - FADUGBA, Abimbola Elizabeth; OYETAYO, Victor Olusegun; OSHO, Bamidele Innocent; OLANIYI, Oladipupo Oladiti (ABUAD Journal of Engineering and Applied Sciences, 2023)
Health and performance are important aspects in the broiler industry. The promotion of good, healthy products and environmental friendly wastes from poultry is the target of sustainable development goals. The effects of feed supplemented with mushroom enriched with minerals in broiler faeces have not been investigated. This experiment was conducted to study the potential effects of iron and Selenium fortified P.ostreatus on microbial load and types associated with faecal droppings of broilers fed mushroom-formulated feed. This experiment was conducted to study the potential effects of non-fortified, Iron fortified and Selenium fortified P.ostreatus on microbial load and types associated with faecal droppings of broilers fed mushroom formulated feed. This experiment was performed for 42 days on broilers. Dietary treatments include standard basal diet as control, non-fortified mushroom feed group (NFM), Iron fortified mushroom feed group (FeFM) and Selenium fortified mushroom feed group (SeFM) at 1.5%, 5% and 10% inclusion levels. Faecal droppings of broilers fed 1.5% NFM feed had the highest bacterial count (2.25 × 107 CFU/g). A total of eleven (11) bacterial and fungal isolates were obtained from the faecal droppings and these are: Micrococcus luteus, Proteus vulgaris, Bacillus subtilis, Staphylococcus epidermidis and Staphylococcus aureus. The fungal isolates incudes: Aspergillus sp, Fusarium sp, Rhizopus sp and Candida sp. Staphylococcus aureus and Staphylococcus epidermidis were observed to be absent in the faeces of broilers fed 1.5% NFM and SeFM dietary treatments. Fusarium solarium was absent in the faecal sample of broilers fed NFM, Candida tropicalis was not present in the faeces of broilers fed FeFM while Candida tropicalis and Rhizopus stolonifer were observed to be absent in SeFM (1.5%, 5% and 10%) respectively. Feeding broilers with mushroom fortified feed at all inclusion levels 1.5%, 5% and 10% had observable decrease on microbial loads and types of broiler faecal droppings. Fortification of mushroom with minerals could reduce the level of microorganisms released into the ecosystem through poultry droppings that finds its way to the final consumers, humans.